Georgia : Staff Report for the 2006 Article IV Consultation, Third Review Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2006)
This 2006 Article IV Consultation highlights that Georgia's economy has performed well over the last two years, and the fiscal turnaround has been impressive. Since the change in government in late 2003, Georgia has demonstrated strong fiscal performance and a renewed commitment to press ahead with structural reforms, including the privatization of state-owned enterprises and further legal, fiscal, and financial reforms. Executive Directors have welcomed the gains from the far-reaching tax reform enacted by the authorities in 2005 while encouraging them to continue strengthening tax administration.